A novel, flexible dual-mode power generator adapted for wide dynamic range of the aqueous salinity. (July 2021) - Li, Lianhui; Gao, Shouwei; Hao, Mingming; Yang, Xianqing; Feng, Sijia; Li, Lili; Wang, Shuqi; Xiong, Zuoping; Sun, Fuqin; Li, Yue; Bai, Yuanyuan; Zhao, Yangyong; et al.
Abstract: Power generation from working environments involving a time-dependent variation in the ion concentration of the aqueous solution is greatly preferred for many applications. Evaporation-induced hydrovoltaic effect has been demonstrated to serve as a clean, renewable, and sustainable power source, however, such an electricity generation approach is only limited to relatively low ion concentration of fluids. On the other hand, the primary battery is capable of harvesting energy under high salinity conditions, but it becomes ineffective at the low ion concentration. To circumvent the tradeoff, herein we report on the design of a flexible dual-mode electricity nanogenerator (DM-ENG) that can harvest energy from a dynamically-changing aqueous solution. Distinct from existing studies, our DM-ENG is constructed on a highly porous carbon black/PVA film bounded with negatively charged groups, in which the top part is modified as hydrophobic and the bottom being hydrophilic. We show that the generator maintains sustained performances in a wide range of ion concentrations over 10 orders of magnitude. Moreover, the flexible generator exhibits excellent mechanical stability, and can be scaled-up, as evidenced by the output of 101.07 V by the integration of 100 power generators (seawater, 21 °C, 55% RH). Graphical Abstract: A flexible dual-mode electricity nanogenerator (DM-ENG) that can harvest energy from a dynamically-changing aqueous solution was developed. The generator maintains sustained performances in a wide range of ion concentrations over 10 orders of magnitude. Moreover, the flexible generator exhibits excellent mechanical stability, enabling it to be used as a flexible sweat power generator/self-powered sweat sensor for wearable electronics. ga1 Highlights: A flexible dual-mode electricity nanogenerator (DM-ENG) system can directly generate electricity from the ion concentration dynamically-changing solution. A porous carbon black/PVA film was modified into hydrophobic region and hydrophilic region. The DM-ENG system can maintain sustained performances in a wide range of ion concentrations across 10 orders of magnitude. An open circuit voltage of 1.04 V and a short circuit current of 165 μA with an optimized output power of 39.24 μW can be reliably generated in 2 M NaCl under ambient conditions.